Cardiac Cell Membrane-Coated Nanoparticles as a Potential Targeted Delivery System for Cardiac Therapy - Faprathan Pikwong; Jiraporn Kamsarn; Wattanased Jarisarapurin; Phornsawat Baipaywad; Hansoo Park; Sarawut Kumphune (Biomimetics)
Cardiomyopathies, a cause of heart failure, are a predominant cause of death globally and may lead to discernible myocardial abnormalities. Several therapeutic agents were discovered, developed, investigated, and evaluated to save patients’ lives and improve their quality of life. The effective administration of drugs improves therapeutic outcomes while reducing side effects. Nanoparticles (NPs) have been utilised for the delivery of therapeutic agents and demonstrate promise in reducing myocardial ischaemia/reperfusion injury. However, significant limitations of NPs include non-specific targeting and immunogenicity. To improve cardiac targeting and biocompatibility, surface modifications using a cardiac cell membrane (cCM) coating on the surface of NPs have been hypothesised. Here, cCMs were isolated from the human ventricular cell line (AC16), and mesoporous silica nanoparticles (MSNs) were synthesised and then coated with cCMs. The cardiac cell membrane-coated mesoporous silica nanoparticles (cCMCMSNs) did not significantly alter the encapsulation efficiency or the release profile of the loaded drug (Rhodamine B) in comparison to MSN. Moreover, cCMCMSNs demonstrated a significantly enhanced distribution of RhB specifically to cardiac cells, compared to other cell types, without causing cytotoxicity. To evaluate immune escape, cCMCMSNs were exposed to activated macrophages, demonstrating that cCMCMSNs were phagocytosed to a lesser extent than MSN. This study demonstrated the synthesis of cardiac cell membranes coated on the surface of nanoparticles as nanomedicine technologies that enhance selective drug delivery to cardiac cells, potentially offering an alternate method for drug administration in cardiovascular diseases.